Exploring Sources and Infuences of Social Capital on Community College Students' First-Year Success: Does Age Make a Difference?. Issue 10 (October 2018) - Wang, Xueli; Wickersham, Kelly; Lee, Yen; Chan, Hsun-Yu
Background/Context: Although numerous studies have emerged shedding light on community college student success, the enduring role of social capital is often overlooked. Furthermore, when conceptualizing social capital in the community college context and its diverse student population, age represents a unique form of diversity in these institutions that warrants further exploration. Purpose: This research identifies the sources of social capital and the relationships between different sources of social capital and community college success, taking into account how the identified sources and relationships may vary based on age through the following questions: First, what are the major sources of social capital among first-year community college students, and how do sources of social capital vary based on age of students? Second, how do different sources of social capital influence first-year community college success? Third, how do influences of social capital on first-year community college success vary based on the age of students? Research Design: Our study drew on Coleman's conceptualization of social capital, along with survey, administrative, and transcript data from three 2-year colleges in a midwestern state. We performed factor analysis with invariance tests to investigate the sources of social capital among community college students and how the identified factor structure may vary by age. We further conducted a logistic regression to examine the relationship between social capital and community college student success across age. Findings: Our findings indicate that social capital needs to be conceptualized differently for community college students across age because they indeed drew on multiple forms of social capital differently, and the sources of social capital that emerged in turn were related to student success in varied ways. Students under the age of 24 relied on institutional agents and academic interaction as dominant forms of social capital, whereas those over the age of 24 relied on significant other's support. Students under the age of 24 were more likely to succeed if they frequently visited advisors for academic reasons. A low or high level of support for schoolwork was related to a higher chance of success for students between 24 and 29 years of age. For the students who were over 30 years old, a moderate level of engagement in their learning network and discussions with academic advisors was related to the lowest level of dropping out. Conclusions: This study extends the social capital model by illuminating the varying types of social capital that students of different age groups engage with, particularly in the community college context, and pushes the boundaries of the knowledge base on how social capital functions in relation to student success in postsecondary education. The findings also elucidate new directions for research, policy, and practice in regard to cultivating and maximizing networks and information for community college students of all ages.